Automated control system for casting process - Kabdullinov, A.M.; Nussupbekov, B.R.; Khassennov, A.K.; Stoev, M.; Karagaeva, M.B. (KSU Publ., 2017)
This article is dedicated to technologies research that require development and implementation in Kazakhstan, able to provide energy sources economy, as well as improvement of sanitary-hygiene and economical indexes of production. But it’s hard to achieve it, if there is no special equipment at enterprises for achieving of this aim. Therefore, the main aim is to design schemes for automated control system and management for technological process for providing of safety and effective functioning of enterprise. To accomplish this goal, we will describe the mathematical model of the regulatory object, as well as investigate the system of automatic regulation for stability. To analyze the relationship between the defining parameters of the cupola process using advanced experience in operating cupola, the latest achievements in the field of mathematical modeling of technical systems and modern computer technology, considering the process as a cybernetic system. The structure of the management system is developed in accordance with the main trends in automation identified during the analytical review.
Құйма үрдісінің автоматтандырылған басқару жүйесі
Автоматизированная система управления процессом литья
Keywords: mathematical description; stability research; automated system; casting manufacture